2012
DOI: 10.18632/aging.100477
|View full text |Cite
|
Sign up to set email alerts
|

Age dependent increase in the levels of osteopontin inhibits skeletal muscle regeneration

Abstract: Skeletal muscle regeneration following injury is accompanied by rapid infiltration of macrophages, which play a positive role in muscle repair. Increased chronic inflammation inhibits the regeneration of dystrophic muscle, but the properties of inflammatory cells are not well understood in the context of normal muscle aging. This work uncovers pronounced age-specific changes in the expression of osteopontin (OPN) in CD11b+ macrophages present in the injured old muscle as well as in the blood serum of old injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 35 publications
5
65
0
1
Order By: Relevance
“…2012). To provide an insight into the role of OPN‐a expression on skeletal muscle transcriptomics, we performed transcriptional profiling on muscle tissue sections following intramuscular OPN‐a overexpression in 3‐month‐old BLA/J mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2012). To provide an insight into the role of OPN‐a expression on skeletal muscle transcriptomics, we performed transcriptional profiling on muscle tissue sections following intramuscular OPN‐a overexpression in 3‐month‐old BLA/J mice.…”
Section: Resultsmentioning
confidence: 99%
“…2009) and promote regeneration following acute injury in aged mice (Paliwal et al . 2012). Targeting OPN‐a, but not OPN‐c, signalling in human skeletal muscle might be a useful therapeutic strategy, because OPN does exert some positive effects on skeletal muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paliwal and coworkers [172] reported that age-dependent increases in the levels of osteopontin (OPN) inhibit skeletal muscle regeneration. The transient upregulation of OPN after muscle injury has been demonstrated to play a positive role in overall regeneration [173]; however, in cultured myoblasts, OPN has been shown to inhibit cell migration and differentiation [174] as well as muscle regeneration in mdx mice [175].…”
Section: Muscle Regeneration Is Affected In Aging and Muscle Diseasesmentioning
confidence: 99%
“…Neutrophile Macrophage Lymphocyte T en présence de macrophages de sujets jeunes [41]. Les perturbations dans le recrutement et l'activité des leucocytes peuvent donc nuire à la régénération des muscles vieillissants [42].…”
Section: Mastocyteunclassified